The taxonomy of species assigned to Camptosaurus (Dinosauria: Ornithopoda) - Mcdonald, Andrew T. (Zootaxa, 2011)
The taxonomic affinities of species assigned to Camptosaurus are reassessed in light of firsthand examination of the relevant specimens and a new phylogenetic analysis, the first to incorporate all putative species of Camptosaurus. “Camp- tosaurus” valdensis is found to be an indeterminate dryosaurid. The species C. prestwichii, C. aphanoecetes, and C. depressus differ in several important details from the type species, C. dispar, and are assigned to different genera as Cumnoria prestwichii, Uteodon aphanoecetes gen. et comb. nov., and Osmakasaurus depressus gen. et comb. nov. The recent assignment of O. depressus to the genus Planicoxa is considered unjustified.